PENGARUH KARAKTERISTIK KOMITE AUDIT DAN KUALITAS AUDITOR EKSTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN: STUDI EMPIRIS PADA PERUSAHAAN KEUANGAN YANG TERDAFTAR DI BEI - Ulinuha, Nur Ilma; Putikadea, Insyirah (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the influence of audit committee characteristics and external auditor quality on financial statement quality using multiple linear regression method in IDX listed companies in the financial sub-sector 2020-2022. The research sample consisted of 204 observations selected using Purposive Sampling software Eviews 12. The results of the study show that the variables of audit committee competence, the number of audit committee meetings, and the tenure of the audit committee have a positive and significant influence on the quality of financial reports. Meanwhile, the variables of the independent audit committee, the gender of the audit committee, and the quality of external auditors did not have a significant effect on the quality of financial statements